Mycobacteria-Specific T Cells Are Generated in the Lung During Mucosal BCG Immunization or Infection With Mycobacterium tuberculosis - Basile, Juan I.; Liu, Ruining; Mou, Wenjun; Gao, Yu; Carow, Berit; Rottenberg, Martin E. (Frontiers in Immunology, 2020)
Specific T cell responses are central for protection against infection with M. tuberculosis. Here we show that mycobacteria-specific CD4 and CD8 T cells accumulated in the lung but not in the mediastinal lymph node (MLN) at different time points after M. tuberculosis infection or BCG immunization. Proliferating specific T cells were found in the lung after infection and immunization. Pulmonary, but not MLN-derived CD4 and CD8 T cells, from M. tuberculosis-infected mice secreted IFN- after stimulation with different mycobacterial peptides or PPD. Mycobacteria-specific resident memory CD4 and CD8 T cells (TRM) expressing PD-1 accumulated in the lung after aerosol infection and intratracheal (i.t.) -but not subcutaneous (s.c.)- BCG immunization. Chemical inhibition of recirculation indicated that TRM were generated in the lung after BCG i.t. immunization. In summary, mycobacteria specific-TRM accumulate in the lung during i.t. but not s.c. immunization or M. tuberculosis infection. Collectively our data suggests that priming, accumulation and/ or expansion of specific T cells during BCG immunization and M. tuberculosis infection occurs in the lung.